Molecular Determinants for OMF Selectivity in Tripartite RND Multidrug Efflux Systems - Esther Boyer; Jean Dessolin; Margaux Lustig; Marion Decossas; Gilles Phan; Quentin Cece; Grégory Durand; Véronique Dubois; Joris Sansen; Jean-Christophe Taveau; Isabelle Broutin; Laetitia Daury; et al. (MDPI AG, 2022)
Tripartite multidrug RND efflux systems made of an inner membrane transporter, an outer membrane factor (OMF) and a periplasmic adaptor protein (PAP) form a canal to expel drugs across Gram-negative cell wall. Structures of MexA-MexB-OprM and AcrA-AcrB-TolC, from Pseudomonas aeruginosa and Escherichia coli, respectively, depict a reduced interfacial contact between OMF and PAP, making unclear the comprehension of how OMF is recruited. Here, we show that a Q93R mutation of MexA located in the α-hairpin domain increases antibiotic resistance in the MexAQ93R-MexB-OprM-expressed strain. Electron microscopy single-particle analysis reveals that this mutation promotes the formation of tripartite complexes with OprM and non-cognate components OprN and TolC. Evidence indicates that MexAQ93R self-assembles into a hexameric form, likely due to interprotomer interactions between paired R93 and D113 amino acids. C-terminal deletion of OprM prevents the formation of tripartite complexes when mixed with MexA and MexB components but not when replacing MexA with MexAQ93R. This study reveals the Q93R MexA mutation and the OprM C-terminal peptide as molecular determinants modulating the assembly process efficacy with cognate and non-cognate OMFs, even though they are outside the interfacial contact. It provides insights into how OMF selectivity operates during the formation of the tripartite complex.